Tradisi Mohibadaa: Ritual Kecantikan Perempuan Gorontalo - Iskayanti A. Umar; Moh. Imron Rosidi; Renol Hasan (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
The Mohibadaa tradition is a women’s beauty ritual of Gorontalo that is deeply rooted in local wisdom and continues to be practiced within customary and religious contexts. This ritual integrates natural body treatments, cultural symbolism, and spiritual values that shape women’s identities within the Gorontalo social structure. This study aims to examine the cultural meanings, social functions, and sustainability challenges of the Mohibadaa tradition amid the dynamics of modernity. The research employs a descriptive qualitative method with an ethnographic approach, utilizing literature review, documentation analysis, and interpretative analysis of the ritual’s symbolic meanings. The findings indicate that Mohibadaa functions not only as a traditional beauty practice but also as a medium for identity formation, the strengthening of women’s solidarity, and the internalization of customary and religious values. Despite facing challenges arising from changing lifestyles and the preferences of younger generations, the ritual plays a significant role in preserving local culture. Mohibadaa remains relevant as an adaptive and meaningful symbol of Gorontalo women’s local wisdom.